Creación de una empresa productora y comercializadora de bebidas naturales y nutritivas de maíz mote en la ciudad de Machala. - Cely Zapata, Alberto Yasmany (My University, 2019)
This project is aimed at the analysis and development of a new business idea analyzing all aspects that must be considered to know if it is feasible to implement it, the business idea is described, revealing that it arises at the moment of discarding the water that remains in the completion of the cooking of corn mote, since for cooking corn mote should take the correct hygiene measures so that the resulting water can be consumed following the procedures that arose when knowing that the water boiled It absorbs the vitamins and nutrients provided by mote corn, thus we have a thick water with a particular flavor, which when mixed with a fruit and panela to give a sweeter flavor results in a pleasant drink which guarantees to offer a new purchase option and another natural way of obtaining vitamins and nutrients that allow to increase the physical and mental energy in a natural way, improves Mental alertness, provide faster reactions and greater concentration in the day to day. This business idea was identified thanks to the properties that contain the raw material of this product that is corn (mote), and the need of customers to have a natural drink that provides the vitamins you need besides the satisfaction of drinking a product with a pleasant flavor. The theoretical foundation of the business idea is analyzed by identifying several points of view regarding what we should know about what entrepreneurship is, since when we talk about it we can determine a range of possibilities for the economic growth of society. Among the analyzed points of view, they affirm that "the generation of new companies has become a permanent challenge for the different governmental instances, since there is a need to generate sources of employment and wealth permanently, which contribute to the improvement of the conditions socio-economic aspects of the communities, with the understanding that entrepreneurship is an engine of development. In this context, entrepreneurs become a fundamental axis, since they are the ones who identify the opportunities and act in favor of their use. Thus, the promotion of entrepreneurial activity requires the study of motivations and perceptions of the local context, since, in addition to the universal factors that are described in the literature, there are others more specific to each country related to economic, cultural aspects, educational, as well as the conditions for promoting entrepreneurship and entrepreneurial skills in the population ". The innovative aspect of the business proposal is clearly defined by saying that this product satisfies the need of customers to have a 100% natural energy drink that does not harm health, and that in turn replenishes the energy of those who consume it, its Elaboration is done in an artisan way to achieve that unique flavor of corn (mote) since it is our main raw material for the elaboration of this product. The general and specific objectives that I have set for construction and consolidation of the company are presented, for which we have as a general objective: To develop a company for the production and commercialization of natural and nutritious beverages that provide lasting wellbeing in consumers and as specific objectives we define: Analyze the importance of protecting the health of consumers of beverages, Creation of a production and marketing company of natural and nutritious beverages of corn mote in the city of Machala, Develop a natural product with quality processes, become a company recognized and accepted in the Ecuadorian market for the quality of its product. In addition, it analyzes the assets that the company must have for the proper performance of its business activity, such as the production and marketing of a drink based on mote corn. In addition, it analyzes the assets that the company must have for the proper performance of its business activity, such as the production and marketing of a drink based on mote corn. The organizational structure of the company is defined and, in the same way, the functions that the different areas that make up the organization must perform. The questions and the results of the survey made to the community of the city of Machala are presented, which will be our main market after having obtained our sample to which the survey will be directed.
El presente proyecto está dirigido al análisis y desarrollo de una nueva idea de negocio analizando todos los aspectos que se deben considerar para conocer si es factible la puesta en marcha del mismo, se describe la idea de negocio dando a conocer que surge al momento de desechar el agua que queda en la terminación de la cocción del maíz mote, ya que para la cocción del maíz mote se debe tomar las medidas de higiene correctas para que el agua resultante pueda ser consumida siguiendo los procedimientos que surgieron al conocer que el agua al hervirla absorbe las vitaminas y nutrientes que proporciona el maíz mote, así tenemos como resultado un agua espesa con un sabor particular, que al momento de mezclar con una fruta y panela para dar un sabor más dulce da como resultado una bebida agradable la cual garantiza ofrecer una nueva opción de compra y otra forma natural de obtener vitaminas y nutrientes que permitan aumentar la energía física y mental de manera natural, mejorando el estado de alerta mental, proporcionar reacciones más veloces y mayor concentración en el día a día. Esta idea de negocio se identificó gracias a las propiedades que contiene la materia prima de este producto que es el maíz (mote), y la necesidad de los clientes de tener una bebida natural que le proporcione las vitaminas que necesita además de la satisfacción de beber un producto de un agradable sabor. Se analiza la fundamentación teórica de la idea de negocio identificando varios puntos de vista referentes a lo que debemos saber acerca de lo que es emprendimiento ya que al hablar del mismo se logra determinar un abanico de posibilidades para el crecimiento económico de la sociedad. Entre los puntos de vista analizados afirman que “la generación de nuevas empresas se ha convertido en un reto permanente para las diferentes instancias gubernamentales, por cuanto existe una necesidad de generar fuentes de empleo y riqueza de forma permanente, que coadyuven al mejoramiento de las condiciones socioeconómicas de las comunidades, en el entendido de que el emprendimiento es un motor de desarrollo. En este contexto, los emprendedores se convierten en un eje fundamental, puesto que son ellos los que identifican las oportunidades y actúan en pro de su aprovechamiento. Así pues, el fomento de la actividad emprendedora requiere del estudio de motivaciones y percepciones propios del contexto local, ya que, además de los factores universales que se describen en la literatura, existen otros más específicos de cada país relacionados con los aspectos económicos, culturales, educativos, así como las condiciones de fomento al emprendimiento y las capacidades emprendedoras en la población”. Se define claramente el aspecto innovador de la propuesta de negocio al decir que este producto satisface la necesidad de los clientes de tener una bebida energizante 100% natural que no perjudica la salud, y que a su vez repone las energías de quien lo consume, su elaboración es de manera artesanal para lograr ese sabor único del maíz (mote) ya que es nuestra materia prima principal para la elaboración de este producto. Se presentan los objetivos general y específicos que he fijado para construcción y consolidación de la empresa, para lo que tenemos como objetivo general: Desarrollar una empresa para la producción y comercialización de bebidas naturales y nutritivas que proporcionen bienestar duradero en los consumidores y como objetivos específicos definimos: Analizar la importancia de precautelar la salud de los consumidores de bebidas, Creación de una empresa productora y comercializadora de bebidas naturales y nutritivas de maíz mote en la ciudad de Machala, Desarrollar un producto natural con procesos de calidad, llegar a ser una empresa reconocida y aceptada en el mercado ecuatoriano por la calidad de su producto. Además, se analiza los activos con los que debe contar la empresa para el correcto desempeño de su actividad empresarial como lo es de producción y comercialización de una bebida a base de maíz mote. Se define la estructura organizacional de la empresa y de la misma manera las funciones que deben desempeñar las diferentes áreas que componen la organización. Se presentan las preguntas y los resultados de la encuesta realizada a la comunidad de la ciudad de Machala el cual será nuestro principal mercado luego de haber obtenido nuestra muestra al cual será dirigida la encuesta.
Keywords: EMPRENDIMIENTO; BEBIDAS NATURALES; IDEA DE NEGOCIO; INNOVACIÓN DE NEGOCIOS